How does Internet use impact the mental health of social assistance recipients in China? Examining the chain mediating role of social support and family resilience - Wu, Bin; Tian, Beihai (Frontiers in Psychology, 2025)
IntroductionPrevious studies have explored the relationship between Internet use and mental health, but there has been a lack of focus on social assistance recipients. Additionally, there has been insufficient discussion on the impact mechanisms of social support and family resilience on this relationship. This study aims to fill these gaps. Using data from social assistance recipients in China, this study analyzes the relationship between Internet use and the mental health of social assistance recipients and its mechanisms based on the Mindsponge Theory and Conservation of Resources Theory.MethodsThis study used multiple linear regression models and PROCESS models to complete data analysis on 765 Chinese social assistance recipients samples to test the hypothesis. All analyzes were performed using SPSS26.0 and MPlus 8.0.ResultsThe empirical analysis shows that Internet use positively correlates with the mental health of social assistance recipients, and social support and family resilience mediate between Internet use and mental health. In addition, social support and family resilience also play a chain mediating role in the relationship between Internet use and mental health.DiscussionThe analysis results of this study support our hypothesis. Combined with the findings of this study, we discussed the theoretical significance, practical significance, limitations, and future research directions of this study.